Role of left uterine placement in maternal care bundle for the prevention of spinal anesthesia-induced hypotension in cesarean section - Amira Abd El Fattah Shaban Mohammed; Eman A Salem; Abdelrhman Alshawadfy (Wolters Kluwer Medknow Publications, 2021)
Background Hypotension is the most common serious scenario in patients undergoing cesarean sections under spinal anesthesia. Care bundles have been employed using a set of three to five approaches with the aim to prevent and manage hypotension after spinal anesthesia. This study was conducted to determine the effectiveness of left uterine placement in maternal care bundle for the prevention of spinal anesthesia-induced hypotension in cesarean section. Patients and methods A total of 100 parturients age 25-35 years with American Society of Anesthesia grades I and II, undergoing elective cesarean section under spinal anesthesia, were assigned into two equal groups at random: group A and group B (each group n=50). Both groups were subjected to a bundle of care using 4-mg ondansetron diluted in 10-ml normal saline given slowly intravenous for 5 min before the induction of spinal anesthesia, and spinal anesthesia was initiated using hyperbaric bupivacaine with a constant dose (10 mg), and administration of intravenous ephedrine 9 mg was done after spinal anesthesia had been cited. Group A was subjected to additional parameter in the care bundle, including patient's suitable position with left displacement of the pregnant uterus. Mean arterial blood pressure (MABP) and heart rate (HR) were recorded every 5 min for 45 min after spinal anesthesia. The total ephedrine and atropine requirements were also determined. Results Both groups showed a nonsignificant difference of the MABP and HR at the baseline measurement values. Follow-up of MABP and HR values every 5 min for 45 min after the onset of spinal anesthesia showed a statistically significant decrease in both groups. Overall consumption of ephedrine and atropine showed statistically significant decrease in group A compared with group B (P<0.001 and 0.01, respectively). By comparing the effect size between both groups using Cohen's d test regarding MABP, HR measurements, and total dose of ephedrine and atropine, we found that it had a small effect size. Conclusion The application of left uterine placement is an important and effective parameter in a maternal care bundle for decreasing the incidence of postspinal anesthesia hypotension in parturients undergoing elective cesarean section.